2016
DOI: 10.3390/w8110548
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotions in Drinking Recycled Water

Abstract: Abstract:As global freshwater supplies shrink, recycled drinking water (RDW) has become an increasingly important source of water supply. However, RDW remains an underinvested resource despite being a safe and reliable source of water. The dominant hypothesis is that RDW has been rejected on emotional grounds of disgust, a visceral psychological reaction known as the "yuck" factor. This paper investigates the role of emotions in technical decision-making and applies it to RDW implementation. It tests two speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
(61 reference statements)
0
23
0
Order By: Relevance
“…Among them, Gibson & Burton's study has found that the use purpose of reclaimed water and exposure extent to the human are important factors that affect public willingness to accept reclaimed water reuse [5]. People's nauseous reaction to reclaimed water is the so-called "yuck factor", which has also been found as an important indicator of the willingness of people to accept reclaimed water [6][7][8]. There are also other scholars devoted to discovering the differences at the individual level and predicting the reusability of reclaimed water.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Gibson & Burton's study has found that the use purpose of reclaimed water and exposure extent to the human are important factors that affect public willingness to accept reclaimed water reuse [5]. People's nauseous reaction to reclaimed water is the so-called "yuck factor", which has also been found as an important indicator of the willingness of people to accept reclaimed water [6][7][8]. There are also other scholars devoted to discovering the differences at the individual level and predicting the reusability of reclaimed water.…”
Section: Introductionmentioning
confidence: 99%
“…Only one out of 3300 registered water reclamation projects worldwide, located in Windhoek, Namibia, is for direct potable use [56][57][58]. Widespread public scepticism towards drinking treated wastewater can be attributed to emotional grounds of disgust, a visceral psychological reaction known as the 'yuck' factor [59,60]. As an approach to reduce drought vulnerability, it remains to be seen if Singapore can eventually complete the transition to direct supply of recycled water for potable domestic use.…”
Section: -16 (C7 S5 M13)mentioning
confidence: 99%
“…The reservoirs of drinking water are important areas for the people who depend on them. Therefore, ensuring that drinking water areas remain clean is an important issue in the field of water environmental management, ecological protection, and economic and social growth [3][4][5]. Water environmental safety evaluation is a scientific and effective approach to identifying potential risks, assessing the safety level, and determining the water supply capacity of drinking water source areas [6,7].…”
Section: Introductionmentioning
confidence: 99%